Teen clinics: missing the mark? Comparing pregnancy and sexually transmitted infections rates among enrolled and non-enrolled adolescents. Issue 1 (December 2016) - Shaw, Souradet; Metge, Colleen; Taylor, Carole; Chartier, Mariette; Charette, Catherine; Lix, Lisa; Santos, Rob; Sarkar, Joykrishna; Nickel, Nathan; Burland, Elaine; Chateau, Dan; Katz, Alan; et al.
Abstract Background In Manitoba, Canada, school-based clinics providing sexual and reproductive health services for adolescents have been implemented to address high rates of sexually transmitted infections (STIs) and pregnancies. Methods The objectives of this population-based study were to compare pregnancy and STI rates between adolescents enrolled in schools with school-based clinics, those in schools without clinics, and those not enrolled in school. Data were from the PATHS Data Resource held in the Population Health Research Data Repository housed at the Manitoba Centre for Health Policy. Adolescents aged 14 to 19 between 2003 and 2009 were included in the study. Annualized rates of pregnancies and positive STI tests were estimated and Poisson regression models were used to test for differences in rates amongst the three groups. Results As a proportion, pregnancies among non-enrolled female adolescents accounted for 55 % of all pregnancies in this age group during the study period. Pregnancy rates were 2–3 times as high among non-enrolled female adolescents. Compared to adolescents enrolled in schools without school-based clinics, age-adjusted STI rates were 3.5 times (p  < .001) higher in non-enrolled males and 2.3 times (p  < .001) higher in non-enrolled females. Conclusions The highest rates for pregnancies and STIs were observed among non-enrolled adolescents. Although provision of reproductive and health services to in-school adolescents should remain a priority, program planning and design should consider optimal strategies to engage out of school youth.